2015
DOI: 10.1186/s13045-015-0115-7
|View full text |Cite
|
Sign up to set email alerts
|

DNA methyltransferase 1 functions through C/ebpa to maintain hematopoietic stem and progenitor cells in zebrafish

Abstract: BackgroundDNA methyltransferase 1 (Dnmt1) regulates expression of many critical genes through maintaining parental DNA methylation patterns on daughter DNA strands during mitosis. It is essential for embryonic development and diverse biological processes, including maintenance of hematopoietic stem and progenitor cells (HSPCs). However, the precise molecular mechanism of how Dnmt1 is involved in HSPC maintenance remains unexplored.MethodsAn N-ethyl-N-nitrosourea (ENU)-based genetic screening was performed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 59 publications
0
34
0
Order By: Relevance
“…Dnmt1 serves as a maintenance methyltransferase, copying the methylation pattern from parent to daughter strand during DNA replication and its function is required for cell cycle progression [24][25][26] . Loss of Dnmt1 function results in genomic hypomethylation 27-29 and in developmental contexts and specific organ systems, this often compromises progenitor cell maintenance 24,27,[30][31][32][33] through numerous cellular mechanisms. These include: inducing cell cycle arrest 34,35 , retroelement activation 36-39 , inflammatory responses 33,37,40 , aberrant differentiation 28,31,41-44 and/or p53-mediated apoptosis 34,35 .Utilizing the dnmt1 s872 mutant zebrafish allele 30 , we establish an in vivo requirement for dnmt1 in RSCs.…”
mentioning
confidence: 99%
“…Dnmt1 serves as a maintenance methyltransferase, copying the methylation pattern from parent to daughter strand during DNA replication and its function is required for cell cycle progression [24][25][26] . Loss of Dnmt1 function results in genomic hypomethylation 27-29 and in developmental contexts and specific organ systems, this often compromises progenitor cell maintenance 24,27,[30][31][32][33] through numerous cellular mechanisms. These include: inducing cell cycle arrest 34,35 , retroelement activation 36-39 , inflammatory responses 33,37,40 , aberrant differentiation 28,31,41-44 and/or p53-mediated apoptosis 34,35 .Utilizing the dnmt1 s872 mutant zebrafish allele 30 , we establish an in vivo requirement for dnmt1 in RSCs.…”
mentioning
confidence: 99%
“…The inability of rnf4 SIMs mutants to rescue granulopoiesis suggested that an undefined SUMOylated negative regulator of c/ebpa might contribute to the defective phenotype. Our previous work has reported that c/ebpa expression is negatively regulated by DNMT1 through promoter methylation in zebrafish HSPC development (20). It is also well known that SUMOylation can significantly enhance DNMT1 activity (17).…”
Section: Dnmt1-c/ebpa Axis Is Impaired In Primitive and Definitive Grmentioning
confidence: 98%
“…A large number of these TFs, such as GATA1, CCAAT/enhancer-binding protein a (C/ EBPa), and IKAROS, have been characterized as SUMO targets (13)(14)(15)(16). Furthermore, SUMOylation of a series of epigenetic modifiers, including DNA methyltransferase (DNMT) family members (17), have been shown to be crucial in normal and malignant hematopoiesis (18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Uhrf1 is necessary to recruit Dnmt1 to unmethylated DNA during replication (Bostick et al, 2007;Muto et al, 2002;Sharif et al, 2007), and Dnmt1 is necessary to maintain intestinal epithelial progenitor cells . Given this interaction, and that expression of Dnmt1 has been documented in zebrafish embryos in developing endoderm (Liu et al, 2015;Rai et al, 2006), we wondered whether Dnmt1 protein is also expressed in EPCs and surrounding intestinal cell types. To address this question, we immunostained transverse sections of phox2b:EGFP-expressing embryos at 34 and 36 hpf with a Dnmt1 antibody.…”
Section: Enteric Progenitors and Surrounding Intestinal Cells Expressmentioning
confidence: 99%